Independent-Nursing Activities: Aromatherapy, Hand Massage, and Music Therapy for Insomnia Elderly. - Mutia Annisa; Dwi Nurviyandari Kusuma Wati (Bulan Sabit Merah Indonesia, 2024)
The elderly are an age group presenting a substantial risk of experiencing sleep problems. About 81.6% of the elderly from the author’s previous research showed poor sleep quality contributed to various diseases. The current approaches regarding sleep hygiene in society are keen to start mostly with an alternative or complementary therapy rather than consuming sleeping pills. Previous studies showed the possibility of strengthening productivity by combining three-intervention of nursing to relax the body and stimulate the brain’s waves for sleeping. This case study aimed to analyze the application of evidence-based practice as the primary intervention in dealing with Insomnia elderly at one of the social institutions in 2019. The procedure was a combination of aromatherapy, hand massage, and music therapy for 30-minute each repetition five times a week for five weeks at the same time for three women with sleep disorders: a Chinese senior (Mrs. S, 79 y/o), a wheelchair user (Mrs. N, 76 y/o), and well-spoken elderly (Mrs. A, 60 y/o). The therapy was measured subjectively and objectively amid participants’ opinions, achievement of nursing outcomes, and the Pittsburgh Sleep Quality Index (PSQI) instrument within three periods. The assessment in PSQI showed a significant-decreasing score for each participant: (1) 19-9-6, (2) 13-9-5, and (3) 18-10-5, respectively, during the pre-mid-post assessment. This modified intervention was provided to enhance the effectiveness of therapy from the previous study such as the lengthy duration, frequency, and scheduling. Social institutions as a form of service for the elderly can encourage nurses or nursing students to apply this combined intervention to overcome the problem of Insomnia. The recommendation is to continue playing passive music at night as a bedtime ritual regularly performed each day. The benefits are reducing pre-bedtime (sleep onset latency), improving sleep quality, and allowing older people to be better and more productive during the day.